Acyclic Triterpenoid Isolated from Alpinia katsumadai Alleviates Formalin-Induced Chronic Mouse Paw Inflammation by Inhibiting the Phosphorylation of ERK and NF-κB - Lim, Hyung Jin (Molecules, 2020)
Chronic and excessive inflammation can destroy host organs and cause inflammatory diseases such as inflammatory bowel disease, asthma, and rheumatoid arthritis. In this study, we investigated the anti-inflammatory effects of Alpinia katsumadai seed-derived 2,3,5,22,23-pentahydroxy-2,6,10,15,19,23-hexamethyl-tetracosa-6,10,14,18-tetraene (PHT) using lipopolysaccharide (LPS)-stimulated J774 cells and a formalin-induced chronic paw inflammation mouse model. The in vitro results showed that PHT exhibited no cytotoxicity and decreased LPS-induced NO secretion. Additionally, PHT inhibited LPS-induced inducible NO synthase (iNOS) and cyclooxygenase 2 (COX2) protein expression. The quantitative real-time PCR results showed that PHT downregulated the gene expression of the proinflammatory cytokines interleukin-1β (IL-1β) and interleukin-6 (IL-6) but not tumor necrosis factor α (TNF-α). PHT inhibited the LPS-induced phosphorylation of extracellular signal-regulated kinase (ERK) and nuclear factor kappa light chain enhancer of activated B cells (NF-κB). In a mouse model, oral administration of 50 mg/kg PHT significantly alleviated both mouse paw thickness and volume. These results indicate that PHT has potential anti-inflammatory effects and should be considered a possible functional material.